PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA TERHADAP KEPUASAAN DAN LOYALITAS PELANGGAN MENGGUNAKAN DMI SEND DI KOTA DUMAI - -, Nur Ainni Rahmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
The research aims to analyze the influence of service quality, price perception on customer satisfaction and loyalty using DMI SEND in Dumai City. This research is quantitative research and primary data was collected using a questionnaire as an instrument to prove the results of the research. The population in this study were Dumai city residents who had used DMI SEND in Dumai city. The sampling technique used was non-probability sampling with purposive sampling with sample criteria that could become correspondents being people who had used DMI SEND in Dumai City at least twice, aged 17 years and over and lived in Dumai City. The subjects of this research were 126 respondents. For data analysis using path analysis with the statistical program for social science (SPSS) 25. The results of the research show that service quality and price perception have a positive and significant effect on customer satisfaction and loyalty in using DMI SEND in Dumai City, service quality has a positive and significant effect on customer loyalty through customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty using DMI SEND in Dumai City in Dumai City. Keywords: service quality, price perception, customer satisfaction, customer loyalty